Starla and Zeg - Berrios, Frank ([United States] : Random House Kids, 2016)
"Meet Blaze, AJ, and all their monster truck friends in this sturdy box featuring four board books and a plastic handle! It's perfect for boys and girls ages 0 to 3 who are on the go!" --.
On board pages.
Keywords: Trucks -- Juvenile fiction; Automobile racing -- Juvenile fiction; Automobile racing; Board books; Trucks; Board books; Fiction; Juvenile works